2015
DOI: 10.1007/s00345-015-1567-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum 17β-estradiol fails as a marker in identification of aggressive tumour disease in patients with localized prostate cancer

Abstract: Pretreatment serum 17β-estradiol (E2) cannot be considered as a suitable marker for aggressive tumour disease in patients with localized prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…At least the latter one was suggested to be higher in diabetes in a previous report (Kronig et al 2017). However, as obesity is a risk factor for lymph node metastasis in PCa (Schnoeller et al 2015), higher body weight in diabetes could have confounded earlier analyses. We now excluded this possibility and ascertained more frequent lymph node infiltration in diabetes independent of body weight.…”
Section: Endocrine-related Cancermentioning
confidence: 82%
“…At least the latter one was suggested to be higher in diabetes in a previous report (Kronig et al 2017). However, as obesity is a risk factor for lymph node metastasis in PCa (Schnoeller et al 2015), higher body weight in diabetes could have confounded earlier analyses. We now excluded this possibility and ascertained more frequent lymph node infiltration in diabetes independent of body weight.…”
Section: Endocrine-related Cancermentioning
confidence: 82%
“…In another study, it was reported that low TTE correlated with high FSH and that both were associated with high-grade tumors (24). A study assessing EST level reported no significant correlation between EST and locally advanced PCa (25). However, our previous EST analysis in a locally advanced PCa (T3a and T3b) group revealed significant correlation between EST and T3b disease (9).…”
Section: Discussionmentioning
confidence: 81%
“…Conversely, within PCa cell lines characterized by a lower ER-α/ER-β ratio, E2 encourages the upregulation of uncoupling proteins (UCPs) and other antioxidant enzymes [110]. As far as we know, no correlation has been established between obesity and high levels of serum E2 with the development, progression, or aggressiveness of PCa [111]. Nonetheless, a more cohesive correlation has been established between the increased expression of adipokines, in particular leptin, in individuals with obesity and the development and progression of PCa (Figure 3).…”
Section: Can Paternal Obesity Be Promoting Pca Development In the Off...mentioning
confidence: 99%